2017
DOI: 10.1002/smll.201603685
|View full text |Cite
|
Sign up to set email alerts
|

Mild Binding of Protein to C2N Monolayer Reveals Its Suitable Biocompatibility

Abstract: The development of biocompatible nanomaterials for smart drug delivery and bioimaging has attracted great interest in recent years in biomedical fields. Here, the interaction between the recently reported nitrogenated graphene (C N) and a prototypical protein (villin headpiece HP35) utilizing atomistic molecular dynamics simulations is studied. The simulations reveal that HP35 can form a stable binding with the C N monolayer. Although the C N-HP35 attractive interactions are constantly preserved, the binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 68 publications
5
52
1
Order By: Relevance
“…These properties may render C 2 N as a promising candidate material for biomedical applications. To date, only a few theoretical studies have been carried out to explore the biocompatibility of C 2 N and indicating that this material is almost non‐nanotoxic toward genetic materials and proteins . The compatibility of this novel 2D nanomaterial with cell membranes has not been evaluated yet to our knowledge, which is critical for its potential biomedical applications in future.…”
Section: Introductionmentioning
confidence: 99%
“…These properties may render C 2 N as a promising candidate material for biomedical applications. To date, only a few theoretical studies have been carried out to explore the biocompatibility of C 2 N and indicating that this material is almost non‐nanotoxic toward genetic materials and proteins . The compatibility of this novel 2D nanomaterial with cell membranes has not been evaluated yet to our knowledge, which is critical for its potential biomedical applications in future.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale drug-delivery systems (DDSs) including inorganic nanoparticles [1, 2], liposomes [3, 4], hydrogels [57], and polymeric nanoparticles [8, 9] (among others) have great promise in tumor diagnosis and treatment. There are often problems with biocompatibility and short systemic circulation times when using these however, and much recent work has focused on using surface modifiers such as poly(ethylene glycol) (PEG) and proteins to ameliorate these issues [1012]. Unfortunately, such PEG or protein modification can also impede the uptake of a DDS by cancer cells [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…20 Meanwhile, our previous studies have demonstrated that a nitrogenized graphene (abbreviated as C 2 N) monolayer is biocompatible to both protein and DNA systems. 21,22 Thus, modifying the graphenic structures by elemental doping is expected to be an efficient way to tune the biological functions of the nanomaterials.…”
Section: Introductionmentioning
confidence: 99%